The Effectiveness of Multimedia Learning of Science Adventure Game “The Adventure of Flora” as Practice Question for Junior High School Students - Laili, Ummiy Fauziyah; Nuriyah, Zidah Chotamy; Syamsudin, Ahmad (Unnes Science Education Journal, 2024)
Learning media is a benchmark for teachers' success in delivering material and managing the class. This research aims to develop a valid, practical and effective learning media “The Adventure of Flora”. This media is a practice question in the form of a website-based learning game  with plant classification material. The type of research used is R&D with a 4D model consisting of definition, design, development, and dissemination. The subjects of this study are 28 students of class VII-A MTsN 1 Kediri City. The research data was analyzed using a likert scale to measure the level of validity and an independent sample t-test to measure the level of effectiveness of a media. The average percentage obtained from the validity test was 91.5% with the category of suitable for use, from the practicality test it got 96% with the category of very practical and from the independent sample t-test it got a score of sig.(2-tailed) 0.000 which means H0 is rejected and Ha is accepted. It can be concluded that a website-based educational game has been produced  that is valid, practical, and has a significant impact when used. Thus, this product can be disseminated to all junior high school students.